1971
DOI: 10.1002/1520-6807(197101)8:1<65::aid-pits2310080116>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The effects of instructions and response time on divergent thinking test scores

Abstract: What a test measures is a function not only of the items on the test, but also of the testing conditions. This study examined the effects of varying instructions and response time in testing for divergent thinking (DT) on both the level of performance and the intercorrelations of D T subscores with each other and with I&. Christensen, Guilford, and Wilson (1957) varied the instructions and the time allowed for completing D T tasks. They found that subjects told to "be clever" responded with more high quality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Task-specific characteristics might make an individual more susceptible to changes in testing context when responding to this task. Van Mondfrans et al (1971) revealed that an untimed condition increased creativity scores on figural tasks, but did not have a significant effect on the scores on verbal tasks. Also, Smith, Michael, and Hocevar (1990) greatly across creativity tasks (artistic, verbal and mathematical), ranging from 1% on verbal tasks to 30% on artistic tasks.…”
Section: Testing Conditionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Task-specific characteristics might make an individual more susceptible to changes in testing context when responding to this task. Van Mondfrans et al (1971) revealed that an untimed condition increased creativity scores on figural tasks, but did not have a significant effect on the scores on verbal tasks. Also, Smith, Michael, and Hocevar (1990) greatly across creativity tasks (artistic, verbal and mathematical), ranging from 1% on verbal tasks to 30% on artistic tasks.…”
Section: Testing Conditionsmentioning
confidence: 87%
“…Adams, 1968;Vernon, 1971), while other studies reported contrary results (e.g. Busse, Blum, & Gutride, 1972;Channon, 1974;Hattie, 1980;Johns et al, 2000;Kogan & Morgan, 1969;Leith, 1972;Van Mondfrans, Feldhusen, Treffinger, & Ferris, 1971;Williams & Fleming, 1969).…”
Section: Testing Conditionsmentioning
confidence: 89%
“…To further complicate this issue, Lero (1974) reported an interaction between particular creativity tests and whether those tests were timed or not timed. Van Mondfrans, Feldhusen, Treffinger, and Ferris (1971) found that the removal of time limits did not have a significant effect on verbal creative performance and that tension produced by evaluation was necessary to ensure a high level of response. However, they also pointed out that only when time limits were relaxed were there high intercorrelations among the various creativity subscores and that these subscores were unrelated to intelligence measures.…”
Section: Evidence Against Untimed Game-like Conditionsmentioning
confidence: 99%
“…Trentham (1972) found that giving model answers along with the usual Torrance manual instructions did not significantly alter scores, McCormack (1975) was not able to confirm Trentham's results. Van Mondfrans, Feldhusen, Treffinger, and Ferris (1971) investigated the effects of four conditions on creative ability: a formal test condition, a take-home test to complete in 4 days, a relaxed, playful game-like condition, and an incubation session prior to administration. On verbal tasks the formal group performed best, whereas on nonverbal tasks the take-home group excelled.…”
Section: Other Conditionsmentioning
confidence: 99%
“…Wallach and Kogan, 1965;Nicholls, 1971), and some support the efficacy of test-like conditions (e.g. Hattie, 1980;Van Mondfrans, Feldhusen, Treffinger, and Ferris, 1971). Other approaches to the issue of pre-administration environmental conditions include using varied test instructions (Christensen, Guilford, and Wilson, 1957;McCormack, 1975), comparing competitive and non-competitive environments (Halpin and Halpin, 1973;Raina, 1968), and investigating the effect of warm-up activities (Hershey and Kearns, 1979;Carroll, 1980).…”
mentioning
confidence: 99%